Reading achievements among students in the United Arab Emirates: A multilevel analysis of PIRLS 2021 - Hanada Taha Thomure; Cherry Zin Oo; Myint Swe Khine (International Journal of Educational Research Open)
This study investigated student- and school-level factors explaining students' reading achievement in the United Arab Emirates (UAE). Using Progress in International Reading Literacy Study (PIRLS) 2021 data, a multilevel modeling analysis was conducted to examine the reading achievement of students in relation to student-level variables (gender, socioeconomic status, students like reading, students confident in reading, and students engaged in reading) and school-level variables (teacher read for enjoyment, teacher send students to library, and library in school, years as principal, and school characteristics). At the student level, all factors, except for students like reading, showed statistically significant effects on students' reading achievement. At the school level, only two variables, teachers sending students to the library and school characteristics, showed statistically significant effects on students' reading achievement. The paper suggests how reading literacy could be improved in this context.